Passenger's choice in responding to inter-city railway operation for Makassar - Parepare line: A conditional logit model based on stated preference method - Ramli, M.I. (IOP Publishing Ltd, 2020)
The present paper aims to model the passenger's choice in responding to the inter-city railway operation for Makassar-Parepare line. The railway line is the first railway track in Eastern Part of Indonesia, and it is still under construction. In this regard, the study attempted to construct the passenger's preferences through a conditional logit model approach based on the stated preference method. The study considered some main attributes of transport mode services, i.e., travel cost, travel time, and frequency. In further, the study also taking account into the model two additional attributes of the mode, i.e., transfer travel time and transfer travel cost. The data collection of the study carried out an interview method using questionnaire sheet based the stated preference method. The study experimented with varying the level of service for the main attributes of the two available travel modes, i.e., railway and private car modes. The study results showed that passengers prefer to choose one of both travel modes when the mode has travel time faster than the other one, as well as for the lower travel cost. In addition, the inter-city travelers more considered the transfer travel cost attribute than the transfer travel time attribute, when they face both travel mode choice, the new railway mode, and the existing private car mode. Â© Published under licence by IOP Publishing Ltd.